Comprehensive study of phase transformation in age-hardening of Mg–3Nd–0.2Zn by means of scanning transmission electron microscopy. (1st August 2015) - Sanaty-Zadeh, A.; Luo, A.A.; Stone, D.S.
Abstract: Effects of thermal history on precipitation behavior and precipitation kinetics in Mg–3Nd–0.2Zn (wt.%) alloy were studied. Microstructure analysis of the aged alloys revealed the presence of new phases in the microstructure in addition to the old description: Super saturated solid solution (SSSS) → G. P. zones → β ″ → β ′ /β 1 → β, reported for Mg–Nd system. In this regard, the sequence of precipitation for the studied alloy was identified as: Super saturated solid solution (SSSS) → Clusters of atoms → G. P. zones (I, II, III) → β ′ → β 2 → β 1 /γ ′ → β. The formation of clusters of solute atoms in this system was confirmed by high angle annular dark field scanning transmission electron microscopy (HAADF-STEM) and atom probe tomography analysis. In addition, new metastable phases designated as G. P. zones (I, II, III) and β 2 were identified in the microstructure of the aged alloys by means of high resolution HAADF-STEM. The β 2 phase was found to be a transition phase in transformation of β ′ to β 1 . Furthermore, the microstructure analysis revealed that the structure of β 1 phase is indeed a body centered tetragonal structure in spite of face centered cubic structure that has been reported for this phase in the literature.